1950-1980 dönemi Türk resminde tema ve uslüp ayrışmaları - Kılıç, Sibel (My University, 2008)
1950-1980 Dönemi Türk Resminde Tema ve Üslup Ayrışmaları adlı bu çalışma , kendi içerisinde araştırmanın sistematize edilmesine olanak tanıması açısından onar yıllık dilimlere ayrılmıştır. Ayrıca formel olarak belirtilmeyen, ancak çalışmanın bütününden ortaya çıkan doğal sonuç itibarıyla, çalışma iki ana başlık altında toplanmıştır. Bunlardan birincisi, Dünya’da ve Türkiye’de meydana gelen ve toplumun yaşayış, düşünüş ve siyasi gidişatında köklü değişimlere yol açan olayların ve oluşumların, diğer tüm alanlara olduğu gibi resim sanat ortamına dolaylı ve dolaysız etkilerdir. Bu bölüm; Türk resim sanatçılarının konu başlığımıza esas olan , tematik yönden ayrıştırma modelini oluşturmakta olup, dönem sanat ortamının ve sanatçılarının algı ve dikkatlerinin ne denli toplumun ivmesel yönüne dönük olup olmadığının irdelemelerini içermektedir. İkinci bölüm; dönemin sanatçılarının keza konumuzun temel çıkış noktası olan “üslup” yönünden, değişen ve dönüşen yeni dünya düzeninde gündeme gelen sanatsal kutuplaşmalar arasında tuttuğu safların belirlendiği bölümdür. Söz konusu saflar, “Modernist”- “Gelenekçi”- “Sentezci” ve “Bağımsız” adı altında dört ana eğilim çevresinde odaklanmıştır. Söz konusu eğilimlerin etrafında saflaşan sanatçıların tercihlerine etki eden en önemli iki etken, evrensel konseptik bir bakış açısıyla dünyaya entegre olma arzusu ve bu düşünce ile taban tabana zıt olan olan nasyonalist bakış açısıdır. Bunun yanı sıra bu iki zıt kutba da eşit mesafede durarak, yeniliklere sırtını çevirmeksizin yerel ve geleneksel unsurları bir potada eriten sanatçılar ile tüm akım oluşum grup ve eğilimleri bohem ve bağımsız karakterlerine bağlı olarak yadsıyan, kendi iç gerçeklikleri ve dinamiklerinden hız alan sanatçılardan oluşan “bağımsızlar”dır. Çalışmamızı benzerlerinden ayıran ve otantisitesini sağlayan temel unsur, sanatsal eğilim ve akımların tarihsel ve entelektüel hinterlantlarının açılımlarının yapılarak, genel geçer kabul görmüş sınıflandırmalarla önemli ölçüde farklılıklar arz eden tema ve üslup olarak yeni bir ayrıştırma denemesine gidilmesidir. Ayrıştırma denemesinin çekirdek problemini, söz konusu eğilimlerle salt formel olarak yapılan bağdaşımların felsefi hinterlantları ile uyuşma ve örtüşme sorunları oluşturmaktadır. Özellikle “Sentezci ve Toplumcu Gerçekçi” olarak sınıflandırılan sanatçıların söz konusu eğilimlerin kültürel ve politik açılımlarından tam yada yarı bağımsız bir karakter sergiledikleri konusunda tespitler yapılmaya çalışılmıştır. Ana hatları ile özetlenen konuyu bir cümleye indirgemek gerekirse; Türk resim sanat ortamının zorlu dönemeçlerden geçerek geldiği noktada, nitelik olarak değilse de nicel anlamda batı ile arasındaki uçurum diye nitelendirilebilecek binlerce yıllık açığını hızla kapatma çabası içerisinde olduğunu, yazgısına boyun eğmeyen dirayetini ortaya koyarak, her bir onar yıllık dilemler içerisinde önemli yollar kat ettiğini söylemek mümkündür.

In this study, “Style and Theme” differentiation of Turkish painting between 1950-1980 has been investigated into and for the sake of systemization of the study; it has been divided into decades and examined within such a timeframe. Although, the study had been divided into period of decades and despite not being divided into various topics, study has yielded two main outcomes and based on these outcomes, it naturally has been divided into two main sections. First of which is; fundamental changes that have been influencing the social and political life directly or indirectly both in the world and in Turkey and whether to explore the reflections of these changes in our painting as they have been so influential in every aspect of life. As this part forms “a model” which our subject heading is based on “differentiation by theme” this has examined the perceptions of the artists and art-world to see how much of their attention was focused on social momentum of change. As for the other section of the study; transformation of the world, artists and their “style” was the basic origin of our subject examined here in this study as well as polarisation of the artists in relation to these changes taken place. These polarized ranks in question were focused around four main ideas which are “Modernist tendencies, Traditionalist, east-west synthesis and the independents” two main ideological factors effected the preferences of artists ranked into different bi-polar groups were; a-) desire of integration to the universal art world and b-) nationalistic approach in complete contrast to this idea. Along with these two opposite polarised groups, independents seem to have managed to blend best of the both in the same melting pot without turning their back to the new developments taking place in the world. As they have refused all forms of ideologies, they have just formed a concept originating from their inner realities and dynamics that were completely based upon their bohemian lifestyle. The main feature that separates this study from its contemporaries and gives it its authentic characteristics is; artistic trends and tendencies that were assessed by decompressing their intellectual hinterlands and an attempt to form a new “theme and style” classification among Turkish painters. This study has various differences in comparison to earlier works in the same field and strict new code and approach has been adopted in this work which completely denies old-form of approach that is believed to have been deviated from the veracity. The main issue of mentioned differentiation is “compatibility” of the named trends and tendencies with their philosophies as artists had approached and seemed to have absorbed the trend without grasping the underlying philosophy that has generated this particular trend of art. Especially, pro-socialist reality and synthesis style artists seem to have displayed semi-independent character since it is almost certain that they lacked the philosophy backing these artistic trends. As the subject needs to be reduced to a simple one sentence to express the focal point of the work; Turkish painting has reached to this point by passing through a complicated course and although we cannot compare our standing point to the western art in terms of quality, we can comfortably say that our painting can definitely compete with the western painting in terms of quantity. However, despite many years of gap between the progress of Turkish painting and the western painting, it is very important to note the fact that Turkish art hasn’t bowed to its destiny by displaying a strong will in this long learning curve. At the end of every decade examined, progress of the Turkish painting can clearly be noticed in relation to previous decade.
Keywords: Resim Sanatı; Resim_Tarih; Resim, Türk